QUANTITATIVE PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITIES OF SOME CITRUS FRUITS OF SOUTH INDIA - M, Pallavi; Ck, Ramesh; V, Krishna; Parveen, Sameera; L, Nanjunda Swamy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The current investigation was contemplated to evaluate the phytochemicals and in vitro antioxidant activities in peel and pulp of some commercially grown citrus fruits of South India, namely, lemon (Citrus aurantifolia), orange (Citrus reticulata), sour orange (Citrus aurantium), pomello (Citrus grandis), and citron (Citrus medica). Methods: The peel and pulp of the fruits were separated and subjected to cold extraction using 70% alcohol. The extracts obtained were screened for the presence of their phytoconstituents using various qualitative and further quantified for major constituents. Further, the in vitro antioxidant activity was assayed by different radical scavenging methods, namely, 2,2-diphenyl-1-picrylhydrazyl, superoxide anion, nitric oxide, lipid peroxidation inhibition, iron chelating activity, and reducing power assay at different concentrations. Results: All the citrus fruits have shown significant in vitro antioxidant activity for the parameters assessed, wherein peel extracts recorded superior antioxidant potential than their corresponding pulps. The broad range of activity of the extracts suggests that multiple mechanisms mediated by the phytoconstituents are responsible for the antioxidant activity. Conclusion: The study thus revealed that peel and pulp of citrus fruits are potential sources of bioactive compounds which are reflected in antioxidant activity and supports their health-promoting claims of plethora of investigations.